2021
DOI: 10.3389/fnana.2021.728720
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the Catecholaminergic System in the Short-Lived Fish Nothobranchius furzeri

Abstract: The catecholaminergic system has received much attention based on its regulatory role in a wide range of brain functions and its relevance in aging and neurodegenerative diseases. In the present study, we analyzed the neuroanatomical distribution of catecholaminergic neurons based on tyrosine hydroxylase (TH) immunoreactivity in the brain of adult Nothobranchius furzeri. In the telencephalon, numerous TH+ neurons were observed in the olfactory bulbs and the ventral telencephalic area, arranged as strips extend… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 98 publications
(158 reference statements)
1
1
0
Order By: Relevance
“…In contrast, midbrain DA cells have been identified in the tegmental area of cartilaginous fish (Carrera et al, 2005 , 2012 ). Recently, several studies have reported Th-expressing neurons in different actinopterygian species in similar brain regions compared with the neurons we identified in the tegmental part of the midbrain (Lopez et al, 2019 ; Lozano et al, 2019 ; Borgonovo et al, 2021 ). This suggests that our newly identified Th-expressing neurons are not an exclusive feature of zebrafish but may be evolutionary remnants of the midbrain DA neurons found in cartilaginous fish, which are lost or severely reduced in most teleost species.…”
Section: Discussionsupporting
confidence: 74%
“…In contrast, midbrain DA cells have been identified in the tegmental area of cartilaginous fish (Carrera et al, 2005 , 2012 ). Recently, several studies have reported Th-expressing neurons in different actinopterygian species in similar brain regions compared with the neurons we identified in the tegmental part of the midbrain (Lopez et al, 2019 ; Lozano et al, 2019 ; Borgonovo et al, 2021 ). This suggests that our newly identified Th-expressing neurons are not an exclusive feature of zebrafish but may be evolutionary remnants of the midbrain DA neurons found in cartilaginous fish, which are lost or severely reduced in most teleost species.…”
Section: Discussionsupporting
confidence: 74%
“…Since the overall composition of dopaminergic neurons is conserved among teleosts, the distribution of dopaminergic neurons in turquoise killifish is similar to zebrafish and medaka. Please refer to the latest report on the analysis of catecholaminergic neurons in the central nervous system of turquoise killifish [12].…”
Section: Central Nervous System In Small Fishesmentioning
confidence: 99%